2017
DOI: 10.3390/resources6030029
|View full text |Cite
|
Sign up to set email alerts
|

Interannual Variability and Seasonal Predictability of Wind and Solar Resources

Abstract: Solar and wind resources available for power generation are subject to variability due to meteorological factors. Here, we use a new global climate reanalysis product, Version 2 of the NASA Modern-Era Retrospective Analysis for Research and Applications (MERRA-2), to quantify interannual variability of monthly-mean solar and wind resource from 1980 to 2016 at a resolution of about 0.5 degrees. We find an average coefficient of variation (CV) of 11% for monthly-mean solar radiation and 8% for wind speed. Mean C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…The Modern-Era Retrospective analysis for Research and Applications (MERRA) was intended to utilize satellite observations and improve representation of the hydrologic cycle [61]. The current MERRA-2 further incorporated assimilation of aerosol data and of station precipitation observations [62,63], which has led to it being used extensively for studies of wind and solar availability [64][65][66] as well as in studies of global hydrology [67]. The station precipitation data assimilated into MERRA-2 in the Indus basin region are from the Climate Prediction Center Unified Gauge-Based Analysis of Global Daily Precipitation (CPCU) [63].…”
Section: Reanalysesmentioning
confidence: 99%
“…The Modern-Era Retrospective analysis for Research and Applications (MERRA) was intended to utilize satellite observations and improve representation of the hydrologic cycle [61]. The current MERRA-2 further incorporated assimilation of aerosol data and of station precipitation observations [62,63], which has led to it being used extensively for studies of wind and solar availability [64][65][66] as well as in studies of global hydrology [67]. The station precipitation data assimilated into MERRA-2 in the Indus basin region are from the Climate Prediction Center Unified Gauge-Based Analysis of Global Daily Precipitation (CPCU) [63].…”
Section: Reanalysesmentioning
confidence: 99%
“…Energy production of other months can be found in Reference . Also, for the sun, apart from the variations shown that are clear with a high‐frequency statistic, also relevant are the seasonal and interannual variations …”
Section: Nem Solar Inputsmentioning
confidence: 99%
“…Any of these principles can be implemented in the problem of allocation of scarce resources (oil, gas and other mineral resources) in the Arctic region. However, its application requires to take into account the specific conditions necessary to determine both resources in accordance with the requirements of agents [64].…”
Section: Models (Schemes) Of Rationingmentioning
confidence: 99%